A piece of the action : race and labor in post-civil rights Hollywood - Quinn, Eithne, 1971- (Columbia University Press, 2020)
Eithne Quinn reveals how Hollywood catalyzed racial politics in the decade after the passage of the Civil Rights Act, through representation on screen as well as in battles over jobs and resources behind the scenes. Based on extensive archival research and detailed discussions of films, this book examines the limits of Hollywood liberalism.